Continuous-flow meerwein arylation - Bhaya, Vinay G.; Joshi, Ramesh A.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2014)
The continuous-flow Meerwein arylation is demonstrated for a set of few aryl donors (anilines and m-aminoacetophenone) and specific radical acceptors. Homogeneous catalyst (CuBr in HBr and CuCl in HCl) was used to facilitate the reaction. The effect of parameters, viz., temperature, catalyst concentration, residence time, and concentration of the radical acceptor on the yield of the arylated product, was studied. The yield of the aryl derivative obtained by continuous-flow syntheses was always better than the respective experiments in batch mode. Flow synthesis allows easy variation in these parameters and thus allows going close to the maximum possible yields in a system where the relative rates of different reactions create a complex situation. Temperature plays a crucial role by affecting the rates as well as by governing the system homogeneity. The nitrogen bubbles generated in the reaction helped to avoid any channel blockage.
Keywords: diazonium salt; flow chemistry; homogeneous catalyst; Meerwein arylation; micromixer; multistep synthesis

Multi-step synthesis of miltefosine: integration of flow chemistry with continuous mechanochemistry - Patil, Niteen B.; Atapalkar, Ranjit S.; Chavan, Subhash P.; Kulkarni, Amol A. (Chemistry-A European Journal, 2021)
Herein we report for the first time, an advanced continuous flow synthesis of the blockbuster Leishmaniasis drug miltefosine from simple starting materials by a sequence involving four steps of chemical transformation including a continuous mechanochemical step. First three reaction steps were performed in simple tubular reactors in a telescopic mode, while in the last step the product precipitated from the 3(rd) step was used for a continuous mechanochemical synthesis of miltefosine. When compared to a typical batch protocol that takes 15 h, miltefosine was obtained in 58 % overall yield in flow synthesis mode at the laboratory scale in a total residence time 34 min at synthesis rate of 10 g/hr, which is sufficient to treat 4800 patients per day.
Keywords: continuous flow; continuous mechanochemistry; miltefosine; multistep synthesis; reactive intermediates